Impact of hospital volume and surgeon volume on robot‐assisted partial nephrectomy outcomes: a multicentre study. (25th March 2018) - Peyronnet, Benoît; Tondut, Lauranne; Bernhard, Jean‐Christophe; Vaessen, Christophe; Doumerc, Nicolas; Sebe, Philippe; Pradere, Benjamin; Guillonneau, Bertrand; Khene, Zine‐Eddine; Nouhaud, Francois‐Xavier; Brichart, Nicolas; Seisen, Thomas; et al.
Abstract : Objective: To assess the impact of hospital volume (HV) and surgeon volume (SV) on perioperative outcomes of robot‐assisted partial nephrectomy (RAPN). Patients and Methods: All consecutive patients who underwent a RAPN from 2009 to 2015, at 11 institutions, were included in a retrospective study. To evaluate the impact of HV, we divided RAPN into four quartiles according to the caseload per year: low HV (<20/year), moderate HV (20–44/year), high HV (45–70/year), and very high HV (>70/year). The SV was also divided into four quartiles: low SV (<7/year), moderate SV (7–14/year), high SV (15–30/year), and very high SV (>30/year). The primary endpoint was the Trifecta defined as the following combination: no complications, warm ischaemia time (WIT) <25 min, and negative surgical margins. Results: In total, 1 222 RAPN were included. The mean (sd ) caseload per hospital per year was 44.9 (26.7) RAPNs and the mean (sd ) caseload per surgeon per year was 19.2 (14.9) RAPNs. The Trifecta achievement rate increased significantly with SV (69.9% vs 72.8% vs 73% vs 86.1%; P < 0.001) and HV (60.3% vs 72.3% vs 86.2% vs 82.4%; P < 0.001). The positive surgical margins (PSM) rate ( P = 0.02), length of hospital stay (LOS; P < 0.001), WIT ( P < 0.001), and operative time ( P < 0.001), all decreased significantly with increasing SV. The PSM rate ( P = 0.02), LOS ( P < 0.001), WIT ( P < 0.001), operative time ( P < 0.001), and major complications rate ( P = 0.01), all decreased significantly with increasing HV. In multivariate analysis adjusting for HV and SV (model 3), HV remained the main predictive factor of Trifecta achievement (odds ratio [OR] 3.70 for very high vs low HV; P < 0.001), whereas SV was not associated with Trifecta achievement (OR 1.58 for very high vs low SV; P = 0.34). Conclusion: In this multicentre study HV and SV both greatly influenced RAPN perioperative outcomes, but HV appeared to have a greater impact than SV.